Escolha de escola pela família: uma análise exploratória em uma unidade particular de Guarulhos - Souza, Luciana Nogueira de (2018)
The study commences with the finding - based on the School Census (Censo Escolar Inep/MEC) data in recent years – that there is an ever-increasing rate of enrolment in and expansion of the numbers of private primary and private secondary schools in Brazil, and this trend is equally applicable to the state of São Paulo and the city of Guarulhos. However, there are few studies which focus on the choosing of education within the private education sector in our country, especially with regards to the less wealthy population. It is within this context that the present study aims to understand the strategies which families adopt when choosing a private school in the city of Guarulhos. To this end, nine families, which had enrolled their children in the first year of secondary school in 2017, were selected, since the latter education level had the largest number of enrolments. The methodology followed was the use of semi-structured interviews with the families, which were later analysed and categorised from the standpoint of analysis of the discussion arising out of the interviews. The study showed that the procedure used in selecting an education institution is influenced by the perception of what constitutes a good school, as formed by the various life and social experiences undergone by the families. It was shown that the strategies used by the family group in the selection of a school are limited, since they are adopted as a means of avoiding public schools and are restricted by the family's financial situation. Nevertheless, some strategies stood out throughout the school selection process, namely: pedagogical issues, family financial situation, academic environment, geographic location, school staff, infrastructure, and information gathered about the education establishment and its extra-curriculum activities